The degree of availability of creative thinking skills in the science textbook for the fifth grade in the Syrian Arab Republic: The degree of availability of creative thinking skills in the science textbook for the fifth grade in the Syrian Arab Republic (Journal of Hama University, 2025)
The current research aims to determine the creative thinking skills that should be available in the science textbook for the fifth grade prescribed by the Ministry of Education in the Syrian Arab Republic.  And the degree of availability of creative thinking skills (fluency, flexibility, originality, details - elaboration) is defined in the science book. To achieve these goals, the descriptive analytical approach was followed, using a list of creative thinking skills and a content analysis. The list of creative thinking skills included (4) main skills: (fluency, flexibility, originality, and generosity), and (24) sub-indices, so that each main skill includes (6) sub-indices, As for the scientific limits, they are the creative thinking skills in the science book for the fifth grade, prescribed by the Ministry of Education in the Syrian Arab Republic, in addition to the content of the aforementioned book. The time limits for the second semester of the academic year 2023-2024, and the sample is represented by the content of the aforementioned book.The research reached a set of results, the most important of which are: There is a weakness in creative thinking skills in the science book for the fifth grade, as all of them were at a weak degree of availability, as determined by the current research (from 20% and less than 40%). The skill of flexibility was ranked first, the skill of originality was ranked second, the skill of generosity was ranked third, and the skill of fluency was ranked fourth and last. In light of the results, the research presented a set of proposals, including: the need for the Syrian National Center for Curriculum Development to benefit from a list of the main creative thinking skills and their sub-indicators and to set standards to be used during the curriculum development process. Keywords: Creative thinking skills, Science textbook, The fifth grade
Keywords: Creative thinking skills, Science textbook, The fifth grade